Synthesis of diarylpentadienones and pyrazoline derivatives as potential α-glucosidase inhibitor and their antioxidant activities - Adam, Faruk Auwal; Md Razali, Mohammad Aidiel; Rukayardi, Yaya; Mastuki, Siti Nurulhuda; Wei, Leong Sze; Mad Nasir, Nadiah; Mohd Faudzi, Siti Munirah (Malaysian Institute of Chemistry, 2023)
Diabetes mellitus type II (T2DM) is a global public health crisis that can lead to death and disability if poorly treated. T2DM patients are usually prescribed antidiabetic drugs, including α-glucosidase inhibitors (AGIs), but their use can lead to complications. Epidemiological studies have already shown that antioxidant compounds are able to scavenge reactive species and alleviate oxidative stress in T2DM patients. With the main objective of improving the quality of life of T2DM patients, a series of diarylpentadienones (3a-j) and their new pyrazoline derivatives (4a-i) were synthesized and evaluated for their α-glucosidase inhibition and anti-oxidant abilities. The results showed that 5-(4-methoxyphenyl)-1-(5-methylthiophen-2-yl)penta- 2,4-dien-1-one (3h) exhibited significant α-glucosidase inhibition (IC50 40.52 ± 2.0 µM) compared to the standard drug acarbose (IC50 543.80 ± 3.0 µM). While 1-(2,4-dimethoxyphenyl)-5-(4-methoxyphenyl)penta-2,4-dien-1-one (3d) and 1-(3-(3-fluorophenyl)-5-(4-methoxystyryl)-4,5-dihydro-1H-pyrazol-1-yl)ethenone (4f) showed promising radical scavenging potentials of DPPH (96-97) and NO (8-74), which were comparable to the control compounds, quercetin and gallic acid. Molecular docking simulations were then performed to reveal several significant binding interactions of the active molecules with the corresponding protein crystals. It can be concluded that diaryl pentadienone and its pyrazoline derivatives are molecules with potential anti-α-glucosidase and antioxidant properties, but not as dual active compounds, suitable for possible chemical modification according to pharmaceutical requirements in the future.